1998
DOI: 10.1016/s0741-5214(98)70140-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid uptake in expanded polytetrafluoroethylene vascular grafts

Abstract: The occurrence of the membrane permeability may be associated with the dilatation and plastic deformation of the prosthesis. Lipid uptake occurs in ePTFE grafts after an aggressive kinetic process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…16,17 In light of this study, we examined the lipid retention on ePTFE vascular grafts exposed to a phospholipid suspension as a function of various flow conditions. 18 Findings from this study indicated that the lipid uptake depended on the transmural pressure and the time of exposure to the model fluid.…”
Section: Introductionmentioning
confidence: 71%
See 3 more Smart Citations
“…16,17 In light of this study, we examined the lipid retention on ePTFE vascular grafts exposed to a phospholipid suspension as a function of various flow conditions. 18 Findings from this study indicated that the lipid uptake depended on the transmural pressure and the time of exposure to the model fluid.…”
Section: Introductionmentioning
confidence: 71%
“…Lipid uptake on the luminal and external surface of an ePTFE microporous vascular prosthesis exposed to a phospholipid suspension under various flow conditions was analyzed and reported elsewhere. 18 It was demonstrated that the lipids rapidly permeated the prosthesis to gradually agglomerate within the prosthesis wall, thereby inhibiting the further passage of lipids through the membrane. In light of this, the present study focused on examining the lipid sorption across an ePTFE prosthesis wall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A 3% (wt/wt) lipid suspension was obtained by mixing appropriate amounts of phosphatidylcholine (PC) from fresh frozen egg yolk (P‐9671, Sigma Chemical Co., St. Louis, MO, U.S.A.) in double‐distilled deionized water. This particular lipid concentration was chosen because the viscosity of the dispersion closely matched that of blood in similar flow conditions (24), and it provided a good signal in the subsequent FTIR analysis. In fact, even if the 3% concentration was higher than that observed in whole human blood (25), obtaining a good signal from the FTIR spectroscopy was an essential condition, as the focus of this procedure was to detect lipid transport through the prosthesis wall.…”
Section: Methodsmentioning
confidence: 99%